Co‐Evaporated Formamidinium Lead Iodide Based Perovskites with 1000 h Constant Stability for Fully Textured Monolithic Perovskite/Silicon Tandem Solar Cells. Issue 35 (22nd July 2021) - Roß, Marcel; Severin, Stefanie; Stutz, Marvin Björn; Wagner, Philipp; Köbler, Hans; Favin‐Lévêque, Martin; Al‐Ashouri, Amran; Korb, Paul; Tockhorn, Philipp; Abate, Antonio; Stannowski, Bernd; Rech, Bernd; et al.
Abstract: Formamidinium iodide (FAI) based perovskite absorbers have been shown to be ideal candidates for highly efficient and operationally stable perovskite solar cells (PSC). A major challenge for formamidinium lead iodide (FAPbI3 ) is to suppress the phase transition from the photoactive black phase into yellow nonperovskite δ‐phase. Several approaches to stabilize the black phase have been developed for solution‐based perovskites, whereas so far, vacuum‐deposited FAPbI3 has rarely been reported. This study demonstrates the preparation of FAPbI3 by co‐evaporation and discusses the influence of the subjacent hole transporting layer (HTL) on its phase stability. By using FAI excess in the evaporation process in combination with phosphonic acids groups from the HTL, the black perovskite phase is stabilized at room temperature. Further addition of 32–59% methylammonium iodide (MAI) during the co‐evaporation process leads to good absorption properties and high PSC efficiencies of 20.4%. In addition, excellent stability is achieved for optimized MAI to FAI ratios, maintaining 100% of the initial PSC performance after 1000 h under constant operation. This highly stable perovskite composition enables the first monolithic fully textured perovskite/silicon tandem solar cells with co‐evaporated perovskite absorbers. Due to the conformally covered pyramid texture, these tandem cells show minimal reflection losses and reach an efficiency of 24.6%. Abstract : Co‐evaporation methylammonium formamidinium lead iodide perovskites are investigated and different aspects of stability are addressed. The influence of the perovskite composition on the performance and the long‐term stability of the resulting solar cells is studied. Monolithic fully textured perovskite/silicon tandem solar cells with co‐evaporated perovskite absorber are realized. These tandem cells reach an efficiency of 24.6% and exhibit minimal reflection losses.